Two New Records for the Fish Fauna of Simenlik-Akgöl Lagoon in Yeşilırmak River Basin (Samsun-Turkey) - Nazmi Polat; Savaş Yılmaz; Semra Saygın; Melek Özpiçak (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, two new freshwater fish species, Gambusia holbrooki Girard, 1859 and Petroleuciscus borysthenicus (Kessler, 1859) were reported from Simenlik-Akgöl Lagoon in Yeşilırmak Basin (Samsun). Turkey has a rich biodiversity in terms of freshwater fish. Because of climate change, periodic ichthyofauna monitoring and updating of fish fauna are critical. Gambusia holbrooki, Eastern mosquitofish, is an invasive fish species and has a widespread range because of biological struggle against mosquitoes in many water sources. However, simultaneously feeding with fish eggs presents a significant threat to biodiversity. And also, Petroleuciscus borysthenicus, Dnieper chub, is a small bodied-fish from the genus Petroleuciscus with a wide range. Dnieper chub and Eastern mosquitofish were assessed as Least Concern (LC) species according to the IUCN criteria. The minimum and maximum total lengths of P. borysthenicus and G. holbrooki are 4.5 cm-5.7 cm and 2.5 cm-5.3 cm, respectively. The results of this study reveal that the existence of new fish species has been recorded for the fish fauna of Simenlik-Akgöl Lagoon, and the distribution area of both these fish species have reached a different location in Yeşilırmak Basin.